2001
DOI: 10.1046/j.1439-0450.2001.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Antigenic Characterization of Bangladeshi Isolates of Infectious Bursal Disease Virus Demonstrate their Similarities with Recent European, Asian and African Very Virulent Strains

Abstract: Three isolates of infectious bursal disease virus (IBDV), obtained from chickens in Bangladesh in 1999 and designated as BD 1/99, BD 2/99 and BD 3/99, were characterized. In an antigen capture enzyme-linked immunosorbent assay using a panel of VP2-specific neutralizing monoclonal antibodies (mAb), all three isolates showed a mAb-binding profile similar to that of very virulent IBDV (vvIBDV) strains. In contrast to the classical virulent strains, they did not react with mAb 3 and mAb 4. Molecular characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 34 publications
3
39
0
1
Order By: Relevance
“…The 28% mortality induced by isolate 99323 following an experimental 10 4.24 EID 50 challenge in SPF chickens (not significantly different from that induced by strain 89163), the presence in the VP2 protein of 99323 of the four aa found in the typical vvIBDV, and the genetic relatedness between the nt sequences of 99323 and of typical vvIBDVs (as demonstrated by high bootstrap values in the consensus trees) all corroborate the fact that isolate 99323 is indeed a vvIBDV. However in AC-ELISA, the antigenic reactivity of the 99323 isolate was most unusual, as typical vvIBDVs studied until now bound all mAbs but mAbs 3 and 4 (Eterradossi et al, 1997bDi Fabio et al, 1999;Islam et al, 2001). Only three other vvIBDV isolates had been found so far with a modified antigenicity.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The 28% mortality induced by isolate 99323 following an experimental 10 4.24 EID 50 challenge in SPF chickens (not significantly different from that induced by strain 89163), the presence in the VP2 protein of 99323 of the four aa found in the typical vvIBDV, and the genetic relatedness between the nt sequences of 99323 and of typical vvIBDVs (as demonstrated by high bootstrap values in the consensus trees) all corroborate the fact that isolate 99323 is indeed a vvIBDV. However in AC-ELISA, the antigenic reactivity of the 99323 isolate was most unusual, as typical vvIBDVs studied until now bound all mAbs but mAbs 3 and 4 (Eterradossi et al, 1997bDi Fabio et al, 1999;Islam et al, 2001). Only three other vvIBDV isolates had been found so far with a modified antigenicity.…”
Section: Discussionmentioning
confidence: 92%
“…These viruses caused mortality at least twice as high as that induced by the classical serotype 1 viruses (van den Berg et al, 1991;Eterradossi et al, 1992). It has been shown that some Ivorian isolates excepted , the vvIBDV isolates share close genetic relationships in both genome segment A (which encodes IBDV capsid proteins) (Brown et al, 1994) and genome segment B (which encodes virus polymerase) (Islam et al, 2001). Some nucleotide (nt) and the resulting amino acid (aa) changes occurring in segment A have been proposed as the basis for diagnostic tests for the putative vvIBDV, either on an antigenic basis (Eterradossi et al, 1997a,b) or on a molecular basis (Jackwood & Sommer, 1999;.…”
Section: Introductionmentioning
confidence: 99%
“…Classical IBDV strains have worldwide distribution, with some strains capable of causing low mortalities. Very virulent (vv) IBDV strains can cause high mortalities and have spread from Europe to the Middle East, Asia, Africa and South America (Lin et al, 1993;Etterradossi et al, 1999;Kwon et al, 2000;Zierenberg et al, 2000;Ikuta et al, 2001;Islam et al, 2001;Meir et al, 2001). Antigenic variants are predominantly confined to the US, and are highly immunosuppressiv e but do not induce specific mortalities (Lana et al, 1992;Lasher & Shane, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…(Boot et al, 1999); and reverse, 5?-CGC TCG AAG TTR CTC ACC C-3? (Islam et al, 2001). The RT-PCR was performed at the following conditions: RT reaction for 30 min at 528C; denaturation for 30 sec at 958C, 40 cycles with 5 sec at 958C, 10 sec at 578C, and 30 sec at 728C.…”
Section: Methodsmentioning
confidence: 99%